Associations Between Balance Measures and Risk of Fractures in 70-Year-Old Individuals - Nordström, Peter; Ballin, Marcel; Nordström, Anna (The journal of clinical endocrinology and metabolism, 2025)
There are uncertainties regarding to what extent poor vision and distracting tasks reduce balance and are associated with fracture risk. This work aimed to investigate the associations between body sway assessed under different visual and multitasking conditions and later risk of fractures in older adults. This cohort study was conducted in Umeå municipality, Sweden. A total of 5437 community-dwelling 70-year-old individuals participated in a population-based health examination. Body sway at baseline was measured using a Wii balance board in the lateral and anterior-posterior direction during 3 different tests, including with eyes open, dual-tasking, and eyes closed. Fractures during follow-up were ascertained using nationwide registers. During a mean (range) follow-up of 4.8 (0.0-10.6) years, 348 women (12.3%) and 149 men (5.7%) sustained a fracture. In women, both anterior-posterior sway velocity (hazard ratio [HR], 1.05; 95% CI, 1.01-1.08, per mm/s increase) and variation in sway velocity (HR, 1.05; 95% CI, 1.01-1.09, per SD increase) during dual-tasking testing were associated with higher risk of fracture after adjustment for covariates. During testing with eyes closed, all measures of lateral sway were associated with the risk of fracture (P < .01 for all). In men, variation in lateral (HR, 1.03; 95% CI, 1.00-1.07 per SD increase) and anterior-posterior sway velocity (HR 1.05; 95% CI, 1.01-1.10 per SD increase) during dual-tasking testing were associated with higher risk of fracture. Higher body sway velocity and larger variation in sway velocity were associated with a higher risk of fractures both in 70-year-old men and women, especially under more challenging testing conditions.